Chemiluminescent properties of a fluorescent SiC·SiOx composite. Issue 89 (12th September 2016) - Lin, Zhen; Wu, Namei; Yao, Wensong; Chen, Jinyuan; Li, Shaoguang; Liu, Ailin; Lin, Xinhua
Abstract : One-pot hydrothermally synthesized SiC·SiO x has enhancement on the chemiluminescence (CL) from the Ce(iv )–Na2 SO3 system. The increased generation of singlet oxygen and electron–hole annihilation in SiC·SiO x both contributed to the CL emission. Abstract : Chemiluminescence (CL) happened in chemical reactions, in which electronically excited intermediates or products were obtained and subsequently released energy with emission of light. CL is a useful approach to investigate active radicals involved in one system. In the present work, we first found SiC·SiO x, a new kind of zero-dimensional silicon-based nanomaterial, owned CL properties in the presence of Ce(iv )–Na2 SO3 . The CL mechanism was further investigated by the CL, ultraviolet-visible light (UV-vis), and electron spin resonance (ESR) spectra. Mechanistic investigation indicated SiC·SiO x increased the generation of singlet oxygen in the Ce(iv )–Na2 SO3 system and excited SiC·SiO x could be produced from the combination of hole and electron injected SiC·SiO x . This opens up an avenue for investigating the CL properties of SiC·SiO x and promotes their application in various fields.